Urbanization and Structural Transformation of Local Communities in Southeast Asia - Febryan Hidayat; Agus Kusman; Deo Renaldi Saputra; Cahyadi Nugroho (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study synthesizes interdisciplinary scholarship to explain how urbanization and structural transformation reconfigure local communities in Southeast Asia through multi-scalar institutional, spatial, and sustainability dynamics. The analysis demonstrates that economic restructuring, migration, and mega-urban expansion operate as interdependent processes that reshape governance arrangements, inequality patterns, and community agency. Institutional mediation emerges as a critical mechanism translating macro transformation into differentiated social outcomes, while community practices actively renegotiate access to resources and representation. Sustainability transitions further embed ecological constraints within urban development, positioning resilience as a co-produced achievement of governance innovation and collective adaptation. By integrating structural, socio-spatial, and institutional perspectives, the study advances a unified framework that conceptualizes communities as active nodes within evolving urban systems. This framework clarifies how inequality, environmental risk, and governance fragmentation interact across scales, generating adaptive pathways rather than linear outcomes. The findings contribute to urban theory by foregrounding community agency in structural change and offer analytically grounded insights for policy approaches that align economic transformation, social inclusion, and ecological resilience in rapidly urbanizing regions.